Die retoriek van godsdienstige pllitiek in Psalm 2 - Coetzee, J. H. (Verbum et ecclesia, 1998)
The rhetorical argumentation strategies of Psalm 2 as a political-cultic poem are explored in order to highlight the function of these strategies, the exigency and the audience of the initial rhetorical situation. During the creation process of the psalm, the rhetor must have been influenced by the royal court or the king himself, reflecting aspects of the evolutionary process which the Zion theology went through. The rhetor's creation was to be implemented lively during the inauguration ceremony of the Judean king as rhetorical action during which the king (as new rhetor), the world rulers and nations (as universal audience), the Judean audience present at the political-cultic ceremony, as well as Yahweh were engaged in collaborative rhetorical action.